Factors Affecting the Quality of Life of the People with Disabilities in Wathana Nakhon Sa Kaeo Province - Watcharachawakul, Sinlapachai (Mahachula Academic Journal, 2023)
The purposes of this study were to (1) study the level of access to rights of people with disabilities, social support affecting quality of life of people with disabilities in Watthana Nakhon District, Sa Kaeo Province, (2) study the level of quality of Life of people with disabilities in Watthana Nakhon District, Sa Kaeo Province; and3) study the influence of social support on the quality of life of people with disability in Watthana Nakhon District, Sa Kaeo Province. This research is quantitative research, collected data using questionnaires. The sample consisted of 352 people. The statistics used were frequency, percentage, mean, standard deviation, pearson product moment correlation coefficient, and multiple regression analysis. The results of the research showed that (1) the access to the rights of people with disabilities in Watthana Nakhon District, Sa Kaeo Province, as a whole was in the moderate level. Social support for people with disabilities in Watthana Nakhon District, Sa Kaeo Province as a whole was in the moderate level, and (2) the quality of life of the people with disabilities in Watthana Nakhon District, Sa Kaeo Province, as a whole was in the moderate level. The hypothesis testing results showed that social support in all 4 areas was related to the quality of people with disabilities in Watthana Nakhon District, Sa Kaeo Province statistically significant at the 0.05 level and social support affects the quality of life of people with disabilities in Watthana Nakhon District, Sa Kaeo Province with statistical significance at the 0.05 level in all 4 aspects.